2018
DOI: 10.1155/2018/2372305
|View full text |Cite|
|
Sign up to set email alerts
|

Quadratic Integral Sliding Mode Control for Nonlinear Harmonic Gear Drive Systems with Mismatched Uncertainties

Abstract: For a class of nonlinear harmonic gear drive systems with mismatched uncertainties, a novel robust control method is presented on the basis of quadratic integral sliding mode surface, and the closed-loop system has satisfying performance and strong robustness against mismatched uncertainties and nonlinear disturbances. Considering time-varying nonlinear torques and parameters variations which are caused by nonlinear frictions and backlash, a nonlinear harmonic gear drive system mathematic model is established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Zhang (2015) proposed an ISM controller design based on the quadratic integral sliding mode (QISM) for SISO systems with unmatched disturbance. Ding and Xiao (2018) adopted the QISM method to control the nonlinear harmonic gear drive systems. These studies demonstrated that the ISM method has the potential to reject unmatched uncertainty or disturbance if the appropriate format of the ISM is selected.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang (2015) proposed an ISM controller design based on the quadratic integral sliding mode (QISM) for SISO systems with unmatched disturbance. Ding and Xiao (2018) adopted the QISM method to control the nonlinear harmonic gear drive systems. These studies demonstrated that the ISM method has the potential to reject unmatched uncertainty or disturbance if the appropriate format of the ISM is selected.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to analyze the tracking error in detail and design advanced control strategies to compensate for it. In the process of precision machining, internal factors such as servo delay, friction, thrust fluctuation, and vibration, as well as external factors like assembly, wear, and temperature, can all influence tracking error [10][11]. This paper focuses on internal friction disturbance, analyzes its influence on tracking error, and establishes an estimation model and control strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In the article titled "Quadratic Integral Sliding Mode Control for Nonlinear Harmonic Gear Drive Systems with Mismatched Uncertainties" [1], an additional reference should have been cited, which is included in the text below, as reference 19 [2]. Accordingly, the sentence referring to Equation (18) in Section 3, "Quadratic Integral Sliding Mode Design," should read as follows:…”
mentioning
confidence: 99%